2017
DOI: 10.1080/17476348.2017.1391095
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol therapy through high flow nasal cannula in pediatric patients

Abstract: High flow nasal cannula (HFNC) is increasingly used in pediatric patients suffering from respiratory failure. In some disease processes, patients may also benefit from aerosol therapy. Therefore, the use of HFNC to deliver aerosolized medications is a convenient and attractive option. Areas covered: This review aims to appraise available evidence concerning the efficiency of aerosol nebulized therapy delivery using HFNC in pediatric patients. Expert commentary: Delivery of aerosol particles is a very complex p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 44 publications
0
28
0
1
Order By: Relevance
“…Furthermore, when patients need extended periods of aerosol administration, use of mask or mouthpiece is complicated by decreased patient comfort and tolerance. In‐line placement of a nebulizer with HFNC has been described to solve the difficulty and has attracted attention from clinicians in recent years . The survey among American pediatric respiratory therapists showed that 75% of respondents delivered aerosol therapy during HFNC .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, when patients need extended periods of aerosol administration, use of mask or mouthpiece is complicated by decreased patient comfort and tolerance. In‐line placement of a nebulizer with HFNC has been described to solve the difficulty and has attracted attention from clinicians in recent years . The survey among American pediatric respiratory therapists showed that 75% of respondents delivered aerosol therapy during HFNC .…”
Section: Introductionmentioning
confidence: 99%
“…In-line placement of a nebulizer with HFNC has been described to solve the difficulty and has attracted attention from clinicians in recent years. 8,9,[11][12][13] The survey among American pediatric respiratory therapists showed that 75% of respondents delivered aerosol therapy during HFNC. 14 Pediatric patients were reported to be more comfortable and less anxious after inhaling aerosol bronchodilator via HFNC, 8,9 which has also shown the potential benefits of avoiding intubation in a group of pediatric asthma patients, 26% of whom already had acidosis at PICU admission.…”
mentioning
confidence: 99%
“…It has been claimed that vibrating and ultrasonic mesh nebulizers have the ability to make surfactant aerosols without interfering with biochemical composition of medication [48][49][50]. It has been reported that aerosolized surfactant can be delivered using nasal cannula in noninvasive respiratory support [51][52][53][54][55].…”
Section: Mechanical Ventilationmentioning
confidence: 99%
“…The primary mechanism of action for HHFNC is not well known but has many theoretical ones by which it reduces the work of breathing and improves efficiency of ventilation [6,7] by washing out the nasopharyngeal dead space leading to improved alveolar ventilation, reduction in the inspiratory resistance associated with the nasopharynx, improvement in conductance and pulmonary compliance by supplying adequately warmed and humidified gas and provision of positive distending pressure for lung recruitment although the latest is variable [1,8]. Optimal starting flow rate, strategies for weaning, feeding, and use of adjunctive therapy such as nebuliser therapy are some of the unanswered questions while applying HHFNC [9]. Moreover, its use for diseases other than bronchiolitis [10], and during paediatric retrieval is still being explored [11].…”
mentioning
confidence: 99%
“…There is also a limited number of observational studies describing the supportive care of patients receiving HHFNC (i.e. nasogastric (NGT) or nasojejunal tubes (NJT) VS. oral feeding, aerosol delivery techniques for inhalational drug delivery, and use of sedation while on HHFNC) [9,10].…”
mentioning
confidence: 99%